Kekuatan emosi: bagaimana perasaan mempengaruhi keputusan kita - Farikha, Umi (Maliki Interdisciplinary Journal, 2025)
Emotions play a significant role in everyday decision making in both personal and professional contexts. This article discusses how feelings can influence an individual’s decision-making process. Through a literature review and current research, we explore the relationship between emotions and decisions made, and their impact on human behavior. The findings suggest that emotions not only influence the choices made but can also change the way individuals process information. By understanding the power of emotions, we can develop better strategies to make more effective decisions. Understanding how our feelings interact with the decision-making process is an important step to improving the quality of our personal and professional lives. As a suggestion, individuals should strive to recognize their emotions when making important decisions.